Fungus-like mycelial fossils in 2.4-billion-year-old vesicular basalt - Bengtson, S.; Rasmussen, B.; Ivarsson, M.; Muhling, Janet; Broman, C.; Marone, F.; Stampanoni, M.; Bekker, A. (2017)
Fungi have recently been found to comprise a significant part of the deep biosphere in oceanic sediments and crustal rocks. Fossils occupying fractures and pores in Phanerozoic volcanics indicate that this habitat is at least 400 million years old, but its origin may be considerably older. A 2.4-billion-year-old basalt from the Palaeoproterozoic Ongeluk Formation in South Africa contains filamentous fossils in vesicles and fractures. The filaments form mycelium-like structures growing from a basal film attached to the internal rock surfaces. Filaments branch and anastomose, touch and entangle each other. They are indistinguishable from mycelial fossils found in similar deep-biosphere habitats in the Phanerozoic, where they are attributed to fungi on the basis of chemical and morphological similarities to living fungi. The Ongeluk fossils, however, are two to three times older than current age estimates of the fungal clade. Unless they represent an unknown branch of fungus-like organisms, the fossils imply that the fungal clade is considerably older than previously thought, and that fungal origin and early evolution may lie in the oceanic deep biosphere rather than on land. The Ongeluk discovery suggests that life has inhabited submarine volcanics for more than 2.4 billion years.